Kitchen capitalism : microenterprise in low-income households - Sherraden, Margaret S. (SUNY series on urban public policy., 2004)
"Businesses come to life as owners are allowed to speak in their own words in this first in-depth examination of self-employment told from the perspectives of low-income microentrepreneurs. The book systematically analyzes a range of issues, including who chooses to open a micro business, and why; what resources to they bring to their business venture; how well will their venture fare; and what contributes to the growth or decline of their business."--Jacket